Lipid Profile, Glycaemic and Anthropometric Status of Students of a Private Medical College in Dhaka City (Anwer Khan Modern Medical College Journal, 2014)
Over weight and obesity are recognized as recent threat which affecting both developing and developed countries. Obesity and its associated morbidities are leading cause of most noncommunicable diseases. Few recent studies have indicated the presence of increasing in over weight and obesity among children and adolescent but there is no study among adult groups. This cross sectional study was done to assess the prevalence of overweight, obesity and metabolic variables with their relation among medical students. Our result reveals that 8.6% & 1.9% male and 15% & 3.2% female are suffering from overweight and obesity (based on BMI) respectively. More females (31.3% and 65.2%) are centrally obese than males (3.5% and 34.8%) (According to Waist Hip ratio and Waist Height ratio respectively). But according to Waist circumference more males (30.7%) are obese than females (24%). There is also significant difference of male and female BP. DBP & SBP of male (79.22mmHg & 118.9 mmHg) have high normal level than female (72.71mmHg & 108.67mmHg) (P